PENGARUH BRAND IMAGE DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK DAIHATSU XENIA (STUDI PADA PT. KARYA ZIRANG UTAMA DAIHATSU SEMARANG) - Benediktus Hendri Adisaputro; Agung Budiatmo; Hari Susanta Nugraha (Universitas Diponegoro, 2025)
This study aims to examine the influence of brand image and product quality on purchasing decisions for Daihatsu Xenia at PT. Karya Zirang Utama Daihatsu Semarang. Sales data over the past 5 years shows a decline, raising concerns about the instability in Daihatsu Xenia's sales. The study uses a quantitative approach with purposive sampling methods targeting 100 respondents who are Daihatsu Xenia customers. The data was analyzed through classical assumption tests, validity and reliability tests, simple and multiple linear regression analyses, t-tests, and F-tests.The results show that both brand image and product quality significantly influence purchasing decisions for Daihatsu Xenia, both individually and collectively, with a very strong correlation. PT. Karya Zirang Utama Daihatsu is advised to continuously improve product quality and features, utilize creative marketing strategies, provide excellent customer service, and take advantage of automotive exhibitions and test drive events. Additionally, the company needs to implement the latest technology, innovate in vehicle design, and improve quality control during production to ensure that each car meets high standards. With these steps, Daihatsu Xenia's purchasing decisions are expected to increase.Keywords: Brand Image, Product Quality, Purchase Decision